2015
DOI: 10.1186/s12885-015-1904-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of ductal carcinoma in situ of the breast: a systematic review, meta-analysis and meta-regression analysis

Abstract: BackgroundTo summarize data on long-term ipsilateral local recurrence (LR) and breast cancer death rate (BCDR) for patients with ductal carcinoma in situ (DCIS) who received different treatments.MethodsSystematic review and study-level meta-analysis of prospective (n = 5) and retrospective (n = 21) studies of patients with pure DCIS and with median or mean follow-up time of ≥10 years. Meta-regression was performed to assess and adjust for effects of potential confounders – the average age of women, period of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 67 publications
2
59
0
Order By: Relevance
“…This is similar to the situation for local recurrences following DCIS [7][8][9][10][11], and suggests that an in-breast invasive event following a case of DCIS may be better characterized as an invasive local recurrence than as a new primary cancer. However, it is not clear if the distinction between invasive recurrences and invasive primary cancers is clinically relevant.…”
Section: Introductionmentioning
confidence: 49%
“…This is similar to the situation for local recurrences following DCIS [7][8][9][10][11], and suggests that an in-breast invasive event following a case of DCIS may be better characterized as an invasive local recurrence than as a new primary cancer. However, it is not clear if the distinction between invasive recurrences and invasive primary cancers is clinically relevant.…”
Section: Introductionmentioning
confidence: 49%
“…Although survival is excellent with each treatment option, the rates of local recurrence vary widely between the different treatments (7, 11, 21). …”
Section: Standard Treatment Options For Dcismentioning
confidence: 99%
“…Following mastectomy, the theoretical risk of local recurrence of a purely in situ lesion should be essentially zero. However, a low rate of local recurrence has been documented, with a study level meta-analysis of 8 retrospective studies demonstrating an adjusted 10-year local recurrence rate of 2.6% (95% CI 0.8–4.5%) (21). As a pre-invasive lesion, mastectomy may be overtreatment for many women with small, localized DCIS.…”
Section: Standard Treatment Options For Dcismentioning
confidence: 99%
“…Accordingly, a follow-up study for up to 20 years after a biopsy diagnosis of DCIS without subsequent treatment reported that 28% of these patients recurred for IDC within approximately 15 years [7]. This study and other similar reports [3, 8] suggest that some DCIS lesions remain dormant and have a very slow progression rate to IDC. It is also possible that some DCIS lesions do not become invasive.…”
Section: Introductionmentioning
confidence: 68%